Intraocular pressure changes in the intensive care unit: The effect of spontaneous respiration, mechanical ventilation, non-invasive CPAP and medical treatments (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the intraocular pressure (IOP) changes in patients in intensive care unit (ICU) and the parameters that cause these changes.Material and Methods: In total, 304 eyes of 152 patients were examined. IOP and central corneal thickness (CCT) were measured. Age, sex, hospitalization (surgical/non-surgical causes), type of ventilation (spontaneous, intubated, non-invasive continuous positive airway pressure (CPAP), Glasgow coma scale, use of hypertonic solution and sedation status were evaluated.Results: The mean age was 63.52±21.47 (range: 18–96) years, and the male/female ratio was 73/79. The mean hospitalization time was 30.91±47.80 (8-297) days, and the mean Glasgow coma scale score was 9.61±4.42. While 33 patients (21.7%) had hypertonic solution, 28 (18.4%) were sedated. The mean IOP was measured as 13.81±3.58 (6–28) mmHg. In 5 patients, the IOP was more than 20 mmHg, and in 14 patients, it was less than 10 mmHg. It was observed that gender and hospitalization diagnosis had no effect on the IOP change (p=0.97, p=0.814, respectively). When the patients were evaluated according to their respiration types, there was no statistically significant difference in IOP values between patients with spontaneous respiration and intubated patients (p=0.261), but non-invasive CPAP patients were significantly different from patients with spontaneous breathing (p=0.035) and intubated patients (p0.001). In addition, the use of hypertonic solution and sedation significantly decreased IOP (p0.001 in both groups).Conclusion: Some changes in IOP were observed due to some applications in the ICU. These changes are often not significant in patients with no eye problems. However, patients with a glaucoma diagnosis or susceptibility to glaucoma, as well as patients with simultaneous IOP reduction, should be carefully monitored for IOP changes.
Keywords: Glaucoma; hypotony maculopathy; ıntensive care unit; intraocular pressure